2017
DOI: 10.1002/elsc.201700033
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric fluorescent l‐arginine and l‐asparagine biosensors based on the oxazine 170 perchlorate‐ethyl cellulose membrane

Abstract: Ratiometric fluorescent l-arginine (Arg) and l-asparagine (Asn) biosensors were developed using an oxazine 170 perchlorate (O17) ethyl cellulose (EC) membrane and the enzymes entrapped into the matrix of EC and hydrogel polyurethane. The sensing principles were based on the hydrolysis reactions of urea and l-Arg under the catalysis of the urease and arginase to produce ammonia in the case of an l-Argsensing membrane and also on the hydrolysis reaction of l-Asn under the catalysis of asparaginase in the case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
(66 reference statements)
0
6
0
1
Order By: Relevance
“…An et al [95] reported recently the development of ratiometric fluorescent l-arginine and l-asparagine biosensors employing ethyl cellulose membrane, oxazine 170 perchlorate fluorophore, and enzymes immobilized in a matrix of ethyl cellulose membrane and polyurethane hydrogel. The sensory mechanism depended on the hydrolysis reaction of urea and l-arginine in presence of urease and arginase as catalysts.…”
Section: Cellulose-based Fluorescent Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…An et al [95] reported recently the development of ratiometric fluorescent l-arginine and l-asparagine biosensors employing ethyl cellulose membrane, oxazine 170 perchlorate fluorophore, and enzymes immobilized in a matrix of ethyl cellulose membrane and polyurethane hydrogel. The sensory mechanism depended on the hydrolysis reaction of urea and l-arginine in presence of urease and arginase as catalysts.…”
Section: Cellulose-based Fluorescent Biosensorsmentioning
confidence: 99%
“…The biosensing membranes displayed a high quality in terms of the reversibility, stability, and response time. The interference study showed that some constituents, such as amino acids, had slight negative impacts on the efficiency of the biosensing membranes in detecting l-arginine and l-asparagine in both urine and blood samples as well as in the fermentation processes [95,96]. Schyrr et al [97] investigated cellulose nanocrystals as an appropriate material for the simple integration of high-density biological sensors.…”
Section: Cellulose-based Fluorescent Biosensorsmentioning
confidence: 99%
“…The biosensor supplied a potential method for urea-sensing in food safety and clinical diagnostics. Similarly, a ratiometric fluorescent biosensor for l -arginine (Arg) and l -asparagine (Asn) detection was designed by Jong Il Rhee, which was combined oxazine 170 perchlorate (O17)-ethyl cellulose (EC) membrane with enzymes and hydrogel polyurethane (An et al 2017 ). Ammonium ions were produced by the hydrolysis reactions of urea and L-Arg under the catalysis of the urease and arginase, as well as the hydrolysis reaction of L-Asn under the catalysis of asparaginase.…”
Section: Biosensorsmentioning
confidence: 99%
“…Li et al screened asparaginase of ultrahigh thermostability by ammonia detection with Nessler’s reagent . An O17-EC sensing membrane, reacting with the ammonia generated from the reactions through enzyme hydrolysis and changing the proportional fluorescence intensity ratio of λ em 565/λ em 625, was used to detect of l -Arg and l -asparagine . However, ammonium detection is susceptible to environmental interference and affected greatly by cell growth fluctuation.…”
mentioning
confidence: 99%